EMOTIONAL REGULATION IN THE EYES OF SOCIAL WELFARE PROVIDERS - Amores, Argeline Joy (President University, 2025)
This study aimed to understand the perspectives ofÂ five registered social work providers about emotional regulation in terms of positive reframing, boundaries and emotional detachment in the city of Roxas, Capiz for the year 2023-2024. Foreign and local literatures related to emotional regulation were reviewed in relation to the relevance of the study. A validated researcher made semi-structured interview guide was used. Qualitative research methodologyÂ usingÂ phenomenology approach to understand the lived-experience of the participants was utilized. Thematic analysis by Braun & Clarke (2006) was used to analyze and interpret the data. The findings of the study revealed that the understanding of social workers in terms of positive reframing was classified in two themes namely: ultra-positive reframing & intra-positive reframing. The understanding of social workers in terms of boundaries was classified in two themes namely: verbal limitation & non-verbal limitation. The understanding of social workers in terms of emotional detachment categorized in two themes namely: personal related reasons and professional related reasons.